Individualized, Additively Manufactured Drug-Releasing External Ear Canal Implant for Prevention of Postoperative Restenosis: Development, In Vitro Testing, and Proof of Concept in an Individual Curative Trial - Farnaz Matin-Mann; Ziwen Gao; Jana Schwieger; Martin Ulbricht; Vanessa Domsta; Stefan Senekowitsch; Werner Weitschies; Anne Seidlitz; Katharina Doll; Meike Stiesch; Thomas Lenarz; Verena Scheper (MDPI AG, 2022)
Postoperative restenosis in patients with external ear canal (EEC) atresia or stenosis is a common complication following canaloplasty. Our aim in this study was to explore the feasibility of using a three dimensionally (3D)-printed, patient-individualized, drug ((dexamethasone (DEX)), and ciprofloxacin (cipro))-releasing external ear canal implant (EECI) as a postoperative stent after canaloplasty. We designed and pre-clinically tested this novel implant for drug release (by high-performance liquid chromatography), biocompatibility (by the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay), bio-efficacy (by the TNF-α (tumor necrosis factor-alpha)-reduction test (DEX) and inhibition zone test (for cipro)), and microbial contamination (formation of turbidity or sediments in culture medium). The EECI was implanted for the first time to one patient with a history of congenital EEC atresia and state after three canaloplasties due to EEC restenosis. The preclinical tests revealed no cytotoxic effect of the used materials; an antibacterial effect was verified against the bacteria Staphylococcus aureus and Pseudomonas aeruginosa, and the tested UV-irradiated EECI showed no microbiological contamination. Based on the test results, the combination of silicone with 1% DEX and 0.3% cipro was chosen to treat the patient. The EECI was implantable into the EEC; the postoperative follow-up visits revealed no otogenic symptoms or infections and the EECI was explanted three months postoperatively. Even at 12 months postoperatively, the EEC showed good epithelialization and patency. Here, we report the first ever clinical application of an individualized, drug-releasing, mechanically flexible implant and suggest that our novel EECI represents a safe and effective method for postoperatively stenting the reconstructed EEC.